Evaluation of Soft Landscape Elements Integration in Recreational Resorts in South West Nigeria - Morakinyo, Kolawole O.; Abdullahi, Aisha P.; Babalola, Joseph A.; Adedayo, Olatunde F.; Akande, Nneka O. (CV. Gio Architect, 2024)
Nigeria’s environmental sector currently face a significant funding gap. Nigeria has great prospects when it comes to Resort Designs thanks to the diverse landscape, beautiful scenery and many destinations with historic significance. Unfortunately, this is not the case and hence this pose to highlight major problems in Nigeria and possible solutions. The goal of this study is to ascertain the best ways to include soft landscape aspects into resort designs to enhance visitor appeal. In this sense, resorts are independent businesses that aim to provide most of a visitor's needs on the property, including food, drink, housing, sports, entertainment, and shopping. To test the hypothesis that soft landscape elements integrated in resort designs leads to an improved psychological approach on vacationers on such structures, a primary and secondary survey would be carried out to factor out certain data to achieve my aim. Respondents would be randomly divided into two conditions (the vacationers and Staff of several resorts) and asked to respond to an interview guide material. Responses would be concluded and analyzed for my findings using percentages to develop a data to consider for my proposed design. The results gotten from my analysis would be the governing factor to give an insight on how best the integration of soft landscape elements in resort design can be designed. On this basis a good design should therefore be proposed to ensure a proper resort design after proper research and considerations.